Early discharge and home treatment of patients with low-risk pulmonary embolism with the oral factor Xa inhibitor rivaroxaban: an international multicentre single-arm clinical trial. (23rd May 2019) - Barco, Stefano; Schmidtmann, Irene; Ageno, Walter; Bauersachs, Rupert M; Becattini, Cecilia; Bernardi, Enrico; Beyer-Westendorf, Jan; Bonacchini, Luca; Brachmann, Johannes; Christ, Michael; Czihal, Michael; Duerschmied, Daniel; et al.
Abstract: Aims: To investigate the efficacy and safety of early transition from hospital to ambulatory treatment in low-risk acute PE, using the oral factor Xa inhibitor rivaroxaban. Methods and results: We conducted a prospective multicentre single-arm investigator initiated and academically sponsored management trial in patients with acute low-risk PE (EudraCT Identifier 2013-001657-28). Eligibility criteria included absence of (i) haemodynamic instability, (ii) right ventricular dysfunction or intracardiac thrombi, and (iii) serious comorbidities. Up to two nights of hospital stay were permitted. Rivaroxaban was given at the approved dose for PE for ≥3 months. The primary outcome was symptomatic recurrent venous thromboembolism (VTE) or PE-related death within 3 months of enrolment. An interim analysis was planned after the first 525 patients, with prespecified early termination of the study if the null hypothesis could be rejected at the level of α = 0.004 (<6 primary outcome events). From May 2014 through June 2018, consecutive patients were enrolled in seven countries. Of the 525 patients included in the interim analysis, three (0.6%; one-sided upper 99.6% confidence interval 2.1%) suffered symptomatic non-fatal VTE recurrence, a number sufficiently low to fulfil the condition for early termination of the trial. Major bleeding occurred in 6 (1.2%) of the 519 patients comprising the safety population. There were two cancer-related deaths (0.4%). Conclusion: Early discharge and home treatment with rivaroxaban is effective and safe in carefully selected patients with acute low-risk PE. The results of the present trial support the selection of appropriate patients for ambulatory treatment of PE.